Saccharification of lignocellulosic biomass from phoma exigua and ethanol production from saccharomyces cerevisiae using cost effective fabricated Lab scale fermenter - Madhu H N; Manasa V Anand; Gautham Subramaniam; Pradeep R Jain (International Journal of Pharma and Bio Sciences, 2017)
The continued use of petroleum products is now widely considered unsustainable owing to the depletion of fuel reserves and their contribution to global warming. Renewable, efficient and eco-friendly fuels are necessary for environmental and economic sustainability. Our work aims at ethanol production from lignocellulosic materials using the fungus Phoma exigua (P. exigua) and the brewers’ yeast Saccharomyces cerevisiae (S. cerevisiae) for hydrolysis of cellulose to glucose and fermentation of glucose to ethanol respectively. In this project, we have designed and fabricated a fermenter using cost effective materials which facilitates maintenance of the required fermentation conditions including pH, temperature, anaerobic conditions and proper agitation of the media which indeed increases the ethanol yield. From laboratory flask studies we have determined the effect of temperature and pH on the growth of S. cerevisiae, thus finding optimum conditions for its growth. The same conditions were maintained during the fermentation process. Finally, we have carried out a full-fledged fermentation process while maintaining all the optimum conditions using our fabricated fermenter, and spanning a time of 5 days. We have successfully produced ethanol with an encouraging yield of 29.56 mg/ml from wood shavings and 32.01 mg/ml from tissue paper respectively.